Jahn-Teller effect on the structure of the Sm-doped PbTiO3: A theoretical approach - Gurgel, Maria F. C.; Paris, Elaine C.; Espinosa, Jose W. M.; Paiva-Santos, Carlos O.; Leite, Edson R.; Souza, Antonio G.; Varela, José Arana [UNESP]; Longo, Elson [UNESP] (Elsevier B.V., 2007)
Samarium doped PbTiO3 (PT:Sm) and pure PbTiO3 (PT) powders were obtained by polymeric precursor method. These powders were characterized by X-ray diffraction (XRD) and theoretical calculations using the CRYSTAL98 program. The effect of the samarium atom is taken into account only indirectly. The experimental models were compared with the cubic (ideal) and tetragonal theoretical models. The structure deformations existent in the experimental compounds were analyzed from the tiny structural differences that lead to perturbations in the crystal orbital splittings. This paper proposes an efficient alternative methodology for defining structural distortions. (c) 2007 Elsevier B.V. All rights reserved.
Keywords: Ab initio; DFT; lead titanate; samarium; Jahn-Teller effect